Rehydration Compensation of Winter Wheat Is Mediated by Hormone Metabolism and De-Peroxidative Activities Under Field Conditions - Liu, Xuejing; Wang, Xiaodong; Liu, Pan; Bao, Xiaoyuan; Hou, Xiaoyang; Yang, Mingming; Zhen, Wenchao (Frontiers in Plant Science, 2022)
Water deficit and rehydration frequently occur during wheat cultivation. Previous investigations focused on the water deficit and many drought-responsive genes have been identified in winter wheat. However, the hormone-related metabolic responses and de-peroxidative activities associated with rehydration are largely unknown. In this study, two winter wheat cultivars, ‘Hengguan35’ (HG) (drought-tolerant cultivar) and ‘Shinong086’ (SN) (drought-sensitive cultivar), were used to investigate water deficit and the post-rehydration process. Rehydration significantly promoted wheat growth and postponed spike development. Quantifications of specific chemical reagents revealed that rehydration alleviated the peroxidation and osmotic stress caused by water deficit in both cultivars. The wheat cultivar HG showed a better rehydration-compensation phenotype than SN. Phytohormones, including abscisic acid, gibberellin, jasmonic acid, and salicylic acid, were detected using high-performance liquid chromatography and shown to be responsible for the rehydration process. A transcriptome analysis showed that differentially expressed genes related to rehydration were enriched in hormone metabolism- and de-peroxidative stress-related pathways. HG utilized a more sensitive abscisic acid signal transduction and balanced reactive oxygen species pathway than SN to achieve a greater level of rehydration compensation and drought tolerance. In conclusion, we clarified the hormonal changes and transcriptional profiles of drought-resistant and -sensitive winter wheat cultivars in response to drought and rehydration, and we provided insights into the molecular processes involved in rehydration compensation.